EDUCATIONAL PROCESS MODEL DESIGN OF PARTICIPANTS’ SUBJECTIVITY IN THE CONDITIONS OF INFORMATION AND EDUCATION UNIVERSITY ENVIRONMENT - Nadezhda Zavalko; Yelena Feoktistova; Svetlana Sahariyeva (European Scientific Journal, ESJ, 2015)
The paper considers the issue of students’ and teachers’ subjectivity while education process at the university in the conditions of new information society. In the conditions of information and education environment of the university two main subjects of the teacher and the student are connected, as the two interconnected systems, each of which runs its own certain phases in development and formation of subjectivity. Although these two systems have significant differences in the level of education, competence, professionalism, availability of subjective experience, and others, though the development of subjectivity of the student and the teacher are interconnected processes that are developing in parallel. The higher the level of the teacher’s subjectivity is, the higher level of the student’s subjectivity is. And it is not a spontaneous process, it is purposefully controlled. The development process of subjectivity of the main educational process participants in the university can be presented in the form of a spiral. The spiral-shape shows the direction of development. The spiral development is always more complicated than the linear or cyclic. Although on the one hand the process of subjectivity development is a linear process because we move from simpler to more complex forms, and secondly, the development of subjectivity is a cyclical process in which there are certain steps (cycles), step by step alternating.